Development of DiCre parental lineage of Babesia divergens - Reichensdörferová, Dominika (Jihočeská univerzita, 2022)
Babesia divergens is a tick-transmitted parasite of the order Piroplasmida, an important causative agent of bovine and human babesiosis. Even though Babesia represent an important worldwide veterinary threat and an emerging risk to humans, some of the fundamental principles of their parasitic lifestyle are still poorly understood. One of the approaches, which help us to better understand the biology of Babesia parasites and their interaction with hosts or vectors, is functional genomics. Hence, the aim of this thesis is to establish a DiCre parental lineage of B. divergens that may provide the absent genome editing technique of conditional gene knock-out. Such a tool will help to functionally characterize essential genes/proteins and validate them as novel targets for the yet missing specific treatment. We have selected and identified an eligible recipient locus in the B. divergens genome into which a DiCre cassette will be integrated via homology recombination. We have validated and determined the optimal concentration of WR99210 and G-418 for their use as selection markers for transfected B. divergens cultures. Finally, we have designed and constructed the plasmid vector containing the DiCre cassette for the generation of DiCre parental B. divergens lineage that may be universally applicable to functionally validate any genes/proteins of interest.
Development of DiCre parental lineage of Babesia divergens
Keywords: B. divergens; DiCre cassette; DiCre parental B. divergens lineage; treatment; Gibson assembly; B. divergens; DiCre cassette; DiCre parental B. divergens lineage; treatment; Gibson assembly